ANALISIS OPERASIONAL ANGKUTAN UMUM DI KABUPATEN BUTON - AKSA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
Public Passenger Car (MPU) is a mode of land transportation with operating systems operating in various sizes. In the Buton Regency, the fleet is operated by medium-sized buses and small buses for rural transportation. In the operation of the MPU, service to service users is a top priority that must be considered and prioritizes safety that is carried out properly by the operator / owner of the MPU. This study aims to find out and analysis how much the level of expectation and performance of MPU entrepreneurs in Buton Regency on service perceptions, tariffs and routes and to find out and analysis how much the level of expectation and performance of Buton District Transportation Service Officers in MPU services in Buton Regency on service perception , Tariff and Route Analysis of the level of importance and performance in the five dimensions of service quality consisting of reliability, responsiveness, assurance, empathy, physical evidence (Tangible) and perception of tariffs and routes to measure expectations and MPU performance. The data analysis of this research was conducted using a descriptive qualitative method to answer the problem formulation of how the expectations of the operators / owners of MPUs and service users towards MPU operations on perceptions of service quality, tariffs and routes, then used